Find \( f(g(x)) \) and \( g(f(x)) \) and determine whether the pair of functions \( f \) and \( g \) are inverses of each other. \( f(x)=9 x-8 \) and \( g(x)=\frac{x+9}{8} \) a. \( f(g(x))=\square \) (Simplify your answer. Use integers or fractions for any numbers in the expression.)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To find \( f(g(x)) \), we first need to substitute \( g(x) \) into \( f(x) \). We have: \[ g(x) = \frac{x + 9}{8} \] Now, substituting \( g(x) \) into \( f(x) \): \[ f(g(x)) = f\left(\frac{x + 9}{8}\right) = 9\left(\frac{x + 9}{8}\right) - 8 \] Now we can simplify it: \[ = \frac{9(x + 9)}{8} - 8 = \frac{9x + 81}{8} - \frac{64}{8} = \frac{9x + 81 - 64}{8} = \frac{9x + 17}{8} \] So, \[ f(g(x)) = \frac{9x + 17}{8}. \] Now, let's find \( g(f(x)) \) by substituting \( f(x) \) into \( g(x) \): \[ f(x) = 9x - 8 \] Substituting this into \( g(x) \): \[ g(f(x)) = g(9x - 8) = \frac{(9x - 8) + 9}{8} = \frac{9x + 1}{8}. \] So, \[ g(f(x)) = \frac{9x + 1}{8}. \] Now, let's determine if \( f \) and \( g \) are inverses of each other. For \( f \) and \( g \) to be inverses, we need: 1. \( f(g(x)) = x \) 2. \( g(f(x)) = x \) From our calculations: - \( f(g(x)) = \frac{9x + 17}{8} \) (not equal to \( x \)) - \( g(f(x)) = \frac{9x + 1}{8} \) (not equal to \( x \)) Thus, \( f \) and \( g \) are not inverses of each other.